2006
DOI: 10.1042/bj20061020
|View full text |Cite
|
Sign up to set email alerts
|

The Dbs PH domain contributes independently to membrane targeting and regulation of guanine nucleotide-exchange activity

Abstract: Dbl family GEFs (guanine nucleotide-exchange factors) for the Rho GTPases almost invariably contain a PH (pleckstrin homology) domain adjacent to their DH (Dbl homology) domain. The DH domain is responsible for GEF activity, and the PH domain plays a regulatory role that remains poorly understood. We demonstrated previously that Dbl family PH domains bind phosphoinositides with low affinity and cannot function as independent membrane targeting modules. In the present study, we show that dimerization of a Dbs (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 48 publications
1
33
0
Order By: Relevance
“…Similarly, a Dbl mutant that is defective for oligomerization does not affect in vitro GEF activity (27). Our observations that mutants that are oligomerization-defective and chemically induced Cdc24p oligomerization both affect the localization of this exchange factor are consistent with this recent study on Dbs (42). Oligomerization-defective or constitutively oligomerized Cdc24p mutants catalyzed Cdc42p GDP-GTP exchange in vitro similar to wild-type Cdc24p.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Similarly, a Dbl mutant that is defective for oligomerization does not affect in vitro GEF activity (27). Our observations that mutants that are oligomerization-defective and chemically induced Cdc24p oligomerization both affect the localization of this exchange factor are consistent with this recent study on Dbs (42). Oligomerization-defective or constitutively oligomerized Cdc24p mutants catalyzed Cdc42p GDP-GTP exchange in vitro similar to wild-type Cdc24p.…”
Section: Discussionsupporting
confidence: 80%
“…Recently Baumeister et al (42) have shown that chemically induced dimerization of the Dbs DHPH domain is sufficient to alter its subcellular distribution and drive it to the plasma membrane. This effect is presumably because of an increase in avidity of the PH domain interactions with the phosphoinositide phosphatidylinositol 4,5-bisphosphate.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of Dbl family GEFs are located in the cytosol of resting cells, and membrane association is generally accepted to be a prerequisite for nucleotide exchange on Rac. In the case of GEFs homologous to Dbl, the isolated DH-PH tandem alone is sufficient for PM localization and biological activity in vivo (24,25,(51)(52)(53)(54). Therefore, to investigate the possible role of Dbl-related GEFs in Rac1(GDP)⅐ RhoGDI dissociation, we designed a system consisting of DOPC/DOPS or PtdIns(3,4,5)P 3 -enriched DOPC/DOPS liposomes (representing the PM of resting and stimulated phagocytes, respectively), DH-PH tandems of GEF, Rac1(GDP)⅐ RhoGDI complexes, and guanine nucleotides.…”
Section: Discussionmentioning
confidence: 99%
“…For example, proto-Dbl and Dbs both require phosphoinositide binding to the PH domain for membrane recruitment and to maintain their transforming abilities (39,40). The emerging consensus is that the PH domain in the DH/PH tandem often plays a dual role; it can participate in membrane recruitment, and it regulates GEF activity through allosteric interaction with the DH domain and/or the GTPase (41).…”
Section: Discussionmentioning
confidence: 99%